Current developments in robotic assistance technology for total knee arthroplasty: a comprehensive overview - Hongli Zhang; Xing-an Jiang; Bing-chen Jin; Hong-hao Zhang; Jun-bo Liang (Journal of Orthopaedic Surgery and Research)
Abstract Knee arthritis is a common degenerative joint disease, usually with joint swelling, chronic pain, and dysfunction as the main clinical manifestations. At present, the conservative treatment for knee arthritis is mostly using anti-inflammatory and analgesic drugs, but the effect is mostly temporary, and can not prevent its progress and surgery is usually the last treatment method. Total knee arthroplasty, also known as TKA, is one of the most effective treatments for osteoarthritis of the knee that has progressed to the end stage. The inevitable human factor in conventional total knee arthroplasty (TKA) frequently results in poor positioning of the prosthesis during the reconstruction of the lower limb's biomechanical axis. This can lead to severe postoperative pain, accelerated wear of the prosthesis, early loosening, and other problems in the affected knee, which has always been a primary concern for orthopaedic surgeons. Over the course of the past few years, China has gradually begun to develop joint robots. The idea is to plan the surgical plan based on the anatomical structure of the affected limb before the operation, and then to use a mechanical arm and a visual system to assist in the implantation of the prosthesis while the operation is being performed. The treatment costs of robot-assisted technology, on the other hand, vary greatly, and there is still a relatively small amount of high-quality evidence on clinical efficacy. This is because the field of robotic-assisted technology is a relatively new one that has gradually developed over the past few years. In order to provide a fundamental reference for the application value of new treatment methods for advanced knee osteoarthritis, it is necessary to conduct an analysis of the current status of the application of joint robots, as well as the technical advantages and disadvantages that they bring.This narrative study delineates the historical context and current clinical application of robots in knee replacement surgery. An examination of the advantages and disadvantages of RATKA in comparison to TKA offers insights on the prospective application value of the technology. Clinical trial number: Not applicable.